Public policy, entrepreneurship, and venture capital in the United States - Cumming, Douglas; Li, Dan (Journal of Corporate Finance, 2013)
This paper empirically examines business starts, deaths, venture capital and patents in relation to U.S. public policy. The most consistent evidence in the data shows that lower levels of labor frictions and higher levels of SBIR awards are associated with more business starts and higher levels of venture capital per population. Counter to expectations, the data indicate a positive impact from the homestead exemption only among the bottom quartile homestead exemption states, and otherwise a negative impact. We analyze a variety of other policy instruments and compare the effects of policy in regular times with the financial crisis of 2008–2010.